The Effect Of Using Phet's Media On Students' Scientific Methods: Pengaruh Penggunaan Media Phet Terhadap Metode Ilmiah Siswa - Syuhrowardi Syuhrowardi; Fitria Eka Wulandari (Academia Open, 2021)
This study aims to determine the effect of using Phet media on students' scientific methods. The research method used is quantitative pre-experimental to reveal the causal relationship of the use of Phet media to students' scientific methods by involving one group of subjects, the research design one shot cas study was tested on an experimental class using an assessment instrument in the form of an observation sheet of scientific method skills. students in writing to find out the percentage of each indicator of the student's scientific method in writing reports on practical activities using Phet media. Analysis of the data in this study using the calculation of the percentage of each indicator written scientific method observed. The result of this research is the percentage of students' scientific method after being given training using Phet media is 52% with the category of good scientific method. Based on the results of the t-test analysis using the one simple test, it was obtained that a significant value of 0.000 was smaller than the significant level of 0.05 the experimental class had an effect on the students' scientific method. Based on the results of these studies, it can be concluded that there is an effect of using Phet media on students' scientific method skills in writing. Keywords: Media, Phet, Scientific Method